Improving repair management of bucket wheel excavator SRs1200 by application of project management concept - Semolič, Brane (Strojniški vestnik, 2008)
The losses resulting from the defect or breakdown of equipment amount to incredible sums, often far higher than the cost of maintenance, repair or reconstruction. It is for this reason that a large number of methods for maintenance and repair of industrial and other plants have been developed. Elaborated in much detail, these methods nevertheless leave a lot of space for improvement. The improvement is primarily viewed in the context of the management of time, resources and costs of such enterprises. This paper presents a certain concept of project management the implementation of which may improve the maintenance and repair projects. The concept was tested in practice and confirmed in the project of revitalizing of the bucket wheel excavator SRs1200 at MB Kolubara, one of the most complex projects of the kind in the region recently, in terms of technical complexity of reconstruction, the number of participants, the number of activities, cost and time of realization, as well as other elements of the project. The application of this concept allowed for achieving significant results in the technical and financial fields, which will further be analyzed in detail.
Keywords: bagri; vzdrževanje; popravila; projektno vodenje